Mannheimia haemolytica isogenic capsular and LPS-sialylation gene deletion mutants are attenuated in a calf lung challenge model - Harish Menghwar; Fred M. Tatum; Robert E. Briggs; Anna K. Goldkamp; Bradley O. Chriswell; Carly Kanipe; Hao Ma; Eduardo Casas; Rohana P. Dassanayake (Microbiology Spectrum)
ABSTRACT Bovine respiratory disease complex (BRDC) is a multifactorial syndrome that involves complex interactions between environment, bacterial/viral pathogens, and the host. Mannheimia haemolytica is the most significant bacterial pathogen associated with BRDC. This study investigated the virulence of a M. haemolytica serotype 1 capsular-deficient (Δcap) mutant and a M. haemolytica lipopolysaccharide (LPS)-sialylation-deficient (ΔneuA, cytidine monophosphate-sialic acid synthetase) mutant in a calf lung challenge model. Twelve colostrum-deprived calves were divided into three groups (four calves per group) and intratracheally administered inoculum of M. haemolytica wild-type (WT), M. haemolytica Δcap, or M. haemolytica ΔneuA strains (~5 × 108 CFU per animal). Animals were observed for signs of pneumonia and were humanely euthanized 2 to 3 days post-bacterial challenge. Lungs were examined for gross pulmonary lesions, histopathological changes, and bacterial culture. Calves administered WT M. haemolytica exhibited severe lung lesions characterized by extensive consolidation and hemorrhage. In contrast, calves administered M. haemolytica Δcap or M. haemolytica ΔneuA mutants displayed significantly reduced lung lesions (P < 0.05). The most severely affected lung lobes were the right cranial and right middle lobes, with ~50% consolidation. The WT group exhibited significantly higher lung tissue bacterial loads than either of the groups receiving the mutant strains (P < 0.05). The reduced clinical signs, pneumonic lung lesions, and bacterial recovery in the lungs of the calves challenged with either the Δcap or the ΔneuA M. haemolytica mutant strains indicated that these mutations were significantly less virulent than the parent strain.IMPORTANCEWhile Mannheimia haemolytica leukotoxin is well recognized as a major virulence factor, the roles of other possible virulence factors, such as capsule and sialic acid (sialylation of LPS) in M. haemolytica, have not been investigated in animal models. This study revealed that the abolishment of capsule (Δcap) or LPS sialylation (ΔneuA) significantly reduced the virulence of each mutant in calf lung challenges. These results demonstrate that both M. haemolytica capsule and sialylated LPS are important virulence factors that play a key role in the evasion of host defenses.